Whole-Genome Sequence-Based Diversity of Mycobacterium tuberculosis Strains Isolated from a Central Western Region of Mexico - Andrea Monserrat Negrete-Paz; Gerardo Vázquez-Marrufo; Adrián Rodríguez-Carlos; Bruno Rivas-Santiago; Ma. Soledad Vázquez-Garcidueñas (Pathogens)
Tuberculosis remains a significant health issue in Mexico, which has one of the highest incidence rates in the Americas. This study aimed to analyze the circulating sublineages, spoligotypes, drug resistance, and transmission patterns of Mycobacterium tuberculosis in Mexico’s Central Western region using whole-genome sequencing. Seventy-seven Mycobacterium tuberculosis strains underwent phenotypic drug susceptibility testing via MGIT. Genotypic resistance was assessed with TB-Profiler and Mykrobe, while phylogenetic relationships were reconstructed using Snippy and RaxML. SpoTyping identified circulating SITs and families, with a 5-SNP threshold defining genomic transmission clusters. The predominant sublineages were 4.1.1.3 (X-type, n = 19) and 4.1.2.1 (LAM, n = 11), with rare sublineages (EAI5, EAI2-Manila, and Beijing) also observed. Resistance to at least one first-line drug was found in 63.3% of strains, with streptomycin mono-resistance (24.5%) being notable. Multidrug-resistant TB was identified in 16.3% (n = 8) of strains. Five genomic clusters, involving 18.7% of strains, were identified. This study highlights the sublineage diversity in Mexico, emphasizing its importance in global databases and resistance research. The findings, such as SIT47 in GC1, underscore the value of localized genomic studies for effective TB control.